Numerical Simulation & Scene Experiment of Metro Tunnel with Crossover Interval under Fire Conditions. (2017) - Zhu, Pengen; Wei, Weizhi; Mei, Jian; Tu, Jiangfeng; Ding, Ru
Abstract: In this study, numerical simulation and scene experiment with metro crossover interval are performed to estimate the effect of ventilation model and the position of the most unfavorable smoke removal on passenger's life safety under fire conditions. Firstly, based on STESS (Metro Thermal Environment Simulation Software), a network model of smoke removal is established with the crossover interval of metro line 10 (Between Wen De Road Station and Yu Shan Road Station), which discusses the effect on smoke flow and fire spread in different indicators, including fire source position and intensity, the number of platform and interval fan used as dealing with emergency. Secondly, combined with FDS (Fire Dynamics Simulator) technology, a three-dimensional field model of metro station with crossover interval is set up, which contributes to the smoke's variation of temperature field and velocity field as well as concentration field can be simulated and analyzed under fire conditions. And then the model of fire conditions is measured and verified with crossover interval in scene experiment. On the basis of above all, the study puts forward where each opening fan is positioned and what the number is needed, satisfying the requirements of smoke removal and providing references in metro crossover interval at the same time.